INFLUENCE OF SMARTPHONE INTEGRATION ON ACADEMIC PERFORMANCE IN NIGERIAN HIGHER LEARNING INSTITUTIONS - Fatima , Aisha O (Top Educational Review Journal (TERJ), 2023)
The proliferation of smartphones among students in Nigeria has become a noteworthy phenomenon, particularly with the integration of mobile learning devices into higher education curricula. This research examines the impact of smartphone usage on the academic performance of higher learning students. Data was gathered from 91 students through questionnaire schedules and analyzed using descriptive statistics and logit regression. Findings reveal that 51% of respondents are male, and 49% are female. A significant majority (89%) utilize smartphones for both social and academic purposes, with Whatsapp being the predominant social networking platform (70%). The distribution of CGPA among respondents indicates that 45% fall within the range of 2.4-3.49, while only 1% have CGPA below 2.0. Among students who use tablets for both academic and social purposes, 6% achieved a CGPA of 4.5 and above, contrasting with 1% scoring below 2.0. Notably, those who solely use tablets for academic purposes have none with a CGPA of 4.5 and above, but 33.33% within the range of 2.0-4.49. The study identifies the significance of factors such as level of study and average time spent on studying at p<0.05, with primary usage being significant at p<0.1. Recommendations include the full integration of smartphone usage into educational curricula at post-secondary and tertiary levels to enhance academic performance. Additionally, efforts should be made to ensure the affordability and quality of smartphones. Encouraging educators to actively participate in social platforms is suggested to foster enhanced student-teacher interactions and engagements.